Réis, Ruis, Raés, Raos: Frames of Intersubjective Relations of Manggarai People (Philosophical Studies Based on Gabriel Marcel's Concept of Intersubjectivity) - Pandor, Pius; Gon, Videlis; Dominggus, Hyronimus Ario (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The main focus of this article is to explore the wealth of intersubjective values contained in activities réis, ruis, raés, raos Manggarai people. The goal to be achieved is to make local wisdom réis, ruis, raés, raos as a presentation of philosophical thought that contributes to the civilization of rationality of the Indonesian nation. The concept of intersubjectivity in activities réis, ruis, raés, raos occurs because the relationship that is built based on these four activities will become a relationship that is intimate, harmonious, constructive, equal, parallel, and humane-human. To understand and study culture réis, ruis, raés, raos, this article uses Gabriel Marcel's concept of intersubjectivity. The research methodology used is qualitative research with a literature study approach. This study found that réis, ruis, raés, raos are frames of Intersubjective relations of the Manggaraian people. This research contributes to how to overcome the phenomenon of individualism that is rife in the lives of the Manggarai people today due to the lack of exploration and deep meaning of the intersubjective values contained in the activities of réis, ruis, raés, and raos.